A ficha de observação da criança de Helena Antipoff como estratégia de inclusão para as crianças com deficiência na educação infantil - Emanuely Santos Javarrotti (2022)
In Brazil, as in other countries, the education of students with disabilities took place for many years in segregated spaces. Numerous laws, decrees and technical standards were published to guarantee the right to education for children with disabilities. These laws bring several strategies for inclusion, among them is the Individual Development Plan -PDI, whose objective is to promote customized teaching practices based on the specificities of each student. For the construction of the PDI, it is necessary to evaluate the child. Since the beginning of the 20th century, different researchers have dedicated themselves to studies related to child development and children's assessment. Helena Antipoff (1892-1974) was one of these researchers and brought to Brazil great contributions to work with children named at the time as “abnormal”. She developed assessment techniques and instruments, including the 1939 Child Mental Development Observation Form, and its use can support the proposition of important strategies for inclusion. The objective of this study was to retrieve the observation form proposed by Helena Antipoff and compare it to the most current version of the International Classification of Functioning, Disability and Health, following Cieza's connection rules. To this end, this study had two stages, the first aimed at identifying the assessment instruments focused on the child and likely to be used in the educational context, at the level of early childhood education and collection of historical material, and the second, aimed at the connection between the instrument and the ICF. To perform the connection between the form and the ICF, the guides proposed by Cieza et al. were used, which present a series of specific criteria for the adequacy and association between the concepts identified in the instrument items and the categories of the ICF, as well as the version latest version of the ICF. The comparison of the Form with the ICF through Cieza's rules demonstrated that the items on the Form could be coded and related to the structure of the ICF, indicating that the instrument, even being from the year 1939, follows the current trend of evaluating the components of functions of the body with the components of activity and participation, fitting into the biopsychosocial model. In addition, the results showed that the Observation Form can benefit researchers, clinicians, parents and teachers, since the instrument offers the opportunity to obtain information that goes beyond the perspective of the traditional biomedical model. The form helps the kindergarten teacher to get to know the child through its development and thus draw up a specific plan based on the skills that the child has, as well as those that still need to be acquired, subsidizing the PDI proposition and adequacy of the teaching-learning process of the children with disabilities and, consequently, helping the daily teaching practice.